KONSEP PENDIDIKAN TAUHID PADA ANAK USIA DINI - Idhar Idhar (FASHLUNA, 2021)
Parents are the first monotheistic educators for a child in his life, without parental guidance it is impossible for a child to be able to know his god, because one of the foremost gates in educating and guiding his children to know God and implement the values ​​of his god's teachings, because they are the main door his son's success. Parents are the first educators, not only educating or paying attention to their children about general knowledge but more importantly instilling their understanding of religious knowledge even more specifically as well as equipping them. instilling monotheism education which is an obligation as parents. Parents who are responsible for educating children at an early age can be seen from their strength in instilling monotheism in them. Students who are instilled in monotheism at an early age can be seen physically, which is identical with piety, both individually and socially. The purpose of monotheism education is to increase faith and piety as well as noble character in the context of the intellectual life of the nation, which is regulated by law (Article 31 paragraph 3). students in reality like far the fire from roasting. The teaching system provided by the school to its students is mostly only oriented to intellectual intelligence (intelligence) while the inculcation of the values ​​of monotheism in children is very lacking. In this paper, I discuss the discussion of the concept of monotheism education in early childhood.